2015
DOI: 10.1152/jn.00032.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reward feedback accelerates motor learning

Abstract: Recent findings have demonstrated that reward feedback alone can drive motor learning. However, it is not yet clear whether reward feedback alone can lead to learning when a perturbation is introduced abruptly, or how a reward gradient can modulate learning. In this study, we provide reward feedback that decays continuously with increasing error. We asked whether it is possible to learn an abrupt visuomotor rotation by reward alone, and if the learning process could be modulated by combining reward and sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 43 publications
9
152
3
Order By: Relevance
“…Things are not as clear for the Ignore group, but the contingency between the movement and cursor position may have induced participants, either explicitly or implicitly, to modify their behavior because of perceived performance errors (they were instructed that the feedback would always be rotated by 45°). This is especially problematic as mechanisms associated with reward and punishment have been hypothesized to modulate the rate of learning and retention in visuomotor adaptation tasks (Galea, Mallia, Rothwell, & Diedrichsen, 2015; Nikooyan & Ahmed, 2015). Such a modulation of learning or retention could have affected our measures of implicit adaptation in either group.…”
Section: Resultsmentioning
confidence: 99%
“…Things are not as clear for the Ignore group, but the contingency between the movement and cursor position may have induced participants, either explicitly or implicitly, to modify their behavior because of perceived performance errors (they were instructed that the feedback would always be rotated by 45°). This is especially problematic as mechanisms associated with reward and punishment have been hypothesized to modulate the rate of learning and retention in visuomotor adaptation tasks (Galea, Mallia, Rothwell, & Diedrichsen, 2015; Nikooyan & Ahmed, 2015). Such a modulation of learning or retention could have affected our measures of implicit adaptation in either group.…”
Section: Resultsmentioning
confidence: 99%
“…Because participants were instructed to hit the ball as many times as possible within the time duration of each trial, and were provided with a feedback according to this performance measure, we reported their hit rate throughout the experiments. These hits can be considered as reward signals that influence future interception attempts in a reinforcement learning mechanism (Izawa and Shadmehr, 2011; Wolpert et al 2011; Shmuelof et al 2012; Nikooyan and Ahmed, 2015). If the adaptation is error-based (Thoroughman and Shadmehr, 2000; Donchin et al 2003; Smith et al 2006; Herzfeld et al 2014), the candidate error signals need to be identified; for example, the distance between the hand and the paddle at meaningful events during the game such as ball-paddle hits.…”
Section: Discussionmentioning
confidence: 99%
“…Later on the distinction between the evaluative and the informational content of feedback was emphasized (e.g., Annett, 1969). The role of these two types of content can be varied by way of manipulating the kind of feedback (e.g., Heuer and Hegele, 2014;Nikooyan and Ahmed, 2015) or by referring the feedback not only to perfect performance, but also to the best performance reached that far (e.g. SansMuntadas et al, 2014).…”
Section: Mechanisms Of Motor Learningmentioning
confidence: 99%